2016
DOI: 10.1007/s10157-016-1235-2
|View full text |Cite
|
Sign up to set email alerts
|

Circulating antibodies to α-enolase and phospholipase A2 receptor and composition of glomerular deposits in Japanese patients with primary or secondary membranous nephropathy

Abstract: BackgroundPhospholipase A2 receptor (PLA2R) is recognized as a target antigen in primary membranous nephropathy (MN); Anti-α-enolase antibody in primary and secondary MN has been proposed, however, little is known about the potential contribution of α-enolase to the pathogenesis of MN.MethodsWe evaluated circulating antibodies to α-enolase by a dot blotting system and PLA2R by indirect immunofluorescence, and glomerular deposition of these proteins in 25 patients with primary MN, 20 patients with secondary MN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 38 publications
(40 reference statements)
1
19
2
Order By: Relevance
“…[ 7 ] In recent years, some scholars identified reactive epitopes in the CysR, CTLD1, and CTLD7 domains and confirmed the reactivity with soluble forms of each domain: CysR is a major antigen epitope of PLA2R antibodies, but the antigen epitope gradually spreading to CysRCTLD1 and CysRCTLD1CTLD7 with the progress of the disease, and the latter 2 were more closely with the activity of disease. [ 24 ] At present various studies reported serum PLA2R antibodies positive rate of iMN patients ranging from 48% to 82.3%, [ 25 29 ] in which the lowest positive rate (48%) was from Japan, [ 25 ] similar with our study, this phenomenon may have something to do with race and geographic environment. Some scholars pointed out that serum anti PLA2R antibodies even exist in SMN, and the positive rate ranging from 58.8% to 72.3%.…”
Section: Discussionsupporting
confidence: 85%
“…[ 7 ] In recent years, some scholars identified reactive epitopes in the CysR, CTLD1, and CTLD7 domains and confirmed the reactivity with soluble forms of each domain: CysR is a major antigen epitope of PLA2R antibodies, but the antigen epitope gradually spreading to CysRCTLD1 and CysRCTLD1CTLD7 with the progress of the disease, and the latter 2 were more closely with the activity of disease. [ 24 ] At present various studies reported serum PLA2R antibodies positive rate of iMN patients ranging from 48% to 82.3%, [ 25 29 ] in which the lowest positive rate (48%) was from Japan, [ 25 ] similar with our study, this phenomenon may have something to do with race and geographic environment. Some scholars pointed out that serum anti PLA2R antibodies even exist in SMN, and the positive rate ranging from 58.8% to 72.3%.…”
Section: Discussionsupporting
confidence: 85%
“…The clinical sensitivity of the ChLIA exceeded that of ELISA and RC-IFA by 10.4% and 0.7%, respectively, at similar specificities (>99%). The anti-PLA2R-positive rates detected by ChLIA (83.9%), ELISA (73.5%), and RC-IFA (83.2%) were equal to or higher than the prevalence data determined among non-preselected patients with pMN by different methods, such as Western blot (53.0%-81.7%), 10,11 RC-IFA (48.0-82.3%), 12,13 ELISA (50.0-71.8%), 14,15 addressable laser bead immunoassay (51.5-66.9%), 16,17 luciferase immunoprecipitation systems assay (53.3%), 18 and time-resolved fluoroimmunoassay (71.0-89.7%). 19,20 These variations may be due to differences in assay techniques (e.g., epitope exposure, cutoff values, detected Ig subclass) and cohort characteristics (e.g., ethnicity, immunosuppressive treatment).…”
Section: Discussionmentioning
confidence: 70%
“…Antibodies against cytoplasmic alpha-enolase have long been known to be present in the serum of patients with primary and secondary MN (nearly 70%) [ 142 ] but never within the subepithelial deposits [ 143 ]. Antibodies against other cytoplasmic podocyte proteins, including aldose reductase and manganese superoxide dismutase 2, have also been detected in the serum and tissue eluates of microdissected glomeruli in biopsy samples from patients with MN [ 144 ].…”
Section: Other Potentially Pathogenic Antibodiesmentioning
confidence: 99%